Inheritance of yield and fiber length in hybrids cotton of the first generation F1 - Vozhehova Rayisa; Borovyk Vira; Ubaydullaev Jurabek (BIO Web of Conferences)
The patterns of inheritance and variability of economically valuable traits in cotton, manifestations of heterosis, as well as its preservation in hybrid populations with a high inheritance potential during intraspecific and genotypically distant hybridization were determined. Thus, in order to obtain heterosis hybrid combinations in Fl for the “fiber yield” trait, cotton varieties with the same or closele related indicators of this trait were involved in crossing (UF0800038 K 113 / UF0800040 K 111, UF0800038 K 113 /UF0800256 0212). Dominance of one of the parent forms according to the trait “fiber length” in F1 plants is manifested in hybrids that differ sharply in terms of indicators. An intermediate type of trait inheritance was observed in hybrids genotypically close and geographically distant in origin. When studying the variability and inheritance of the trait “fiber length” in parental varieties and their F1 hybrids, it was found that positive overdominance or positive heterosis for the fiber length trait was observed in hybrids with different genotypes and in geographically distant forms. Negative superdominance based on fiber length, i.e. negative heterosis, was found in hybrids with different genotypes and indicators, as well as in samples geographically distant in origin. In general, analyzing the fiber length inheritance data, it can be concluded that the F1 hybrid combinations mainly showed negative and positive overdominance. Therefore, it can be argued that the fiber length in F1 hybrids is mainly regulated by dominant genes.